Lateral Patellar Luxations following Bilateral Hip Joint Replacement in a Dog - Simlett-Moss, Angharad; Arthurs, Gareth; Schiborra, Frederike; Comerford, Eithne (VCOT Open, 2022)
A 2-year-old male neutered crossbreed was presented with a 7-month history of left pelvic limb lameness. Following a diagnosis of bilateral hip dysplasia, staged hybrid total hip replacements (THR) were performed 16 months apart. An ipsilateral grade II lateral patellar luxation (LPL) developed within 24 hours after each THR. Both LPLs were successfully treated by block recession sulcoplasty. Subjective gait analysis showed an abnormal pelvic limb gait following each THR. Clinical examination detected a grade II LPL on each operated limb. Computed tomography of both pelvic limbs revealed mild trochlear sulcus hypoplasia but no other skeletal abnormalities. Trochlear block recession sulcoplasty was performed 10 and 4 weeks respectively after THR. Long-term follow-up 12 months after the last surgery found minimal (0–1/10) lameness, no pain on clinical examination in both PLs and an overall low client-based metrology instrument mobility score of 2 (Liverpool Osteoarthritis in Dogs). This case report documents that in predisposed dogs, with hypoplastic trochlear ridges, LPL can occur secondary to THR and can be successfully managed by standard techniques to address the luxation. Furthermore, despite anecdotal verbal reports of medial patellar luxation occurring secondary to THR in dogs, this is the first published report of the management of any patellar luxation subsequent to THR.
Keywords: total hip replacement; lateral patellar luxation; dogs